Analysis of Services and Promotions to Increase Customer Loyalty Mediated by Customer Satisfaction at Pt. Bank Btpn Putri Hijau Branch - Ryan Dharmawan Laksana; Slamet Widodo; Mesra B (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the factors that affect customer loyalty of Bank BTPN Putri Hijau Branch with a focus on service and promotion. The type of research used is quantitative with a descriptive approach. The analysis method used is Structural Equation Modeling-Partial Least Square (SEM-PLS). The variables studied include Customer loyalty (Y) as a dependent variable, service (X1) and promotion (X2) as independent variables, and Customer satisfaction (Z) as a mediating variable. The results of the study show that services and promotions have a positive and significant effect on customer satisfaction of Bank BTPN Putri Hijau Branch. In addition, service and promotion also have a positive effect on customer loyalty which plays an important role as a mediator between independent variables and customer satisfaction. This research emphasizes the need for Bank BTPN Putri Hijau Branch to continue to improve customer satisfaction, especially in terms of service and promotion. By improving innovative services, Bank BTPN Putri Hijau Branch can improve customer perception, adjust to their lifestyle, and fulfill their motivation to choose BTPN as their flagship bank.